Fostering creativity in school children by teaching of mathematics through creative problem solving - Khalid, Madihah; Saad, Supiah; Abd. Hamid, Siti Rafiah; Abdullah, Muhammad Ridhuan; Ibrahim, Hasniza (National Child Development Research Centre (NCDRC), 2019)
In recent years, there have been growing calls to nurture and teach creativity from an early age in schools. Creativity is not strange in the teaching of arts subjects but is not a common feature in the teaching of STEM subjects. However, it's not the subject, but the approach to it, that teaches creativity. This research was aimed at fostering creativity through the teaching of mathematics. Teaching through problem solving or open-ended approaches which was named as Creative Problem Solving (CPS), was the theme chosen in this research study. A collection of suitable anchor problems that promote creative thinking and lesson plans were developed collaboratively with the teachers through a process called lesson study. This quasi-experimental study investigates changes in students’ as well as teachers after going through the teaching of mathematics via CPS and the process of lesson study respectively. 104 students in the treatment group and 68 students in the comparison group from four (4) schools in the Gombak area were involved in the study. The intervention took about 7 months to complete whereby 3 cycles of lesson study was accomplished, which made up of (3 cycles x 4 schools) 12 lessons altogether. Simultaneously, 17 teachers were involved, together with a few District Education Centre (PPD) officers, which made this study an effective example of synergistic relationship between the three institutions – namely the university, schools and school organizer. An extensive mixed quantitative and qualitative data were collected. Instruments for quantitative data were adopted, adapted and created to suit the context of the study. Torrence Test of Creative Thinking (TTCT) was used to measure students’ creativity before and after intervention, while mathematics problem solving test that was adapted from PISA 2012 questions was used to measure students’ ability in problem solving before and after intervention. Creativity checklist was created and used to evaluate students’ creativity in the four constructs of fluency, flexibility, originality and elaboration by the observers. Qualitative data were collected in the form of observation, students’ and teachers interview, and researchers’ field notes. Students work was also used to explain certain phenomenon. The result of the analysis on observation checklist data shows significant increases in all four constructs of creativity over the three cycles of intervention. There were significant increases in almost all of the creativity domains from cycles 1, 2 and 3. The creativity test shows significant increase in creativity for the treatment group while the increase in the comparison group was not significant. However, ANCOVA fails to suggest that the increase in students’ creativity was due to the treatment. On the other hand, there were significant increases for both treatment and comparison groups in the PISA adapted problem solving test and ANCOVA suggests that the higher difference in increase of the treatment group may have been due to the intervention. This is supported by the correlation analysis, which show very low negative correlation between creativity and problem solving ability before the intervention. However, when the test was run again after the intervention, it was found that there is a significant albeit low relationship between creativity and problem solving ability. The qualitative data was used to support the quantitative results and to investigate teachers’ views on the project and their opinions on the effect of the project on them through lesson study. Students’ responses were encouraging and they communicated their delight in learning through CPS and wish that teachers would teach this way continuously. Meanwhile, the emerging themes from teachers’ interview show their confirmation on how CPS was beneficial to the students and how they have gained from the study in terms of knowledge on pedagogy, content and pedagogical content knowledge of teaching mathematics.